Experimental and theoretical analysis of shear bolted connections for tubular structures. (November 2017) - D'Antimo, M.; Demonceau, J.F.; Jaspart, J.P.; Latour, M.; Rizzano, G.
Abstract: In this paper, numerical and experimental investigations devoted to the evaluation of the bearing resistance of tubular members, with gusset plates and through-all long bolts, are presented. Unlike lap shear joints, the analysed connection shows a limited confinement of the bearing area associated with the use of long bolts and the presence of a gap in the member, which can lead to a reduction of the bearing resistance. In order to investigate the behaviour of shear connections composed by thin or thick SHS (Square Hollow Section) profiles and long bolts, experimental tests on 24 specimens and FE simulations have been conducted. Both experimental and FE results have confirmed the influence of local instability of the hole in bearing on the resistance of thin profiles and the poor accuracy of the available standards for this specific joint typology. In particular, the performed comparisons have shown that, for thin profiles, EC3 model is likely to overestimate the resistance, while for higher thickness of the SHS conservative predictions are obtained. The paper presents the conducted experimental and numerical investigations highlighting, at the end, the need for a proper formulation able to account for the local instability effect on the bearing resistance. Highlights: The results of an experimental programme on 24 connections are reported. EC3 accuracy is checked against experimental data for the analysed connection. A FE model able to predict the bearing resistance is developed and validated. Parametric studies are performed to investigate the effect of the main parameters. The results prove that EC3 is unsafe when local buckling phenomena are influent.